Novel autosomal dominant mandibulofacial dysostosis with ptosis: clinical description and exclusion of TCOF1. Issue 7 (1st July 2002) - Hedera, P; Toriello, H V; Petty, E M
Abstract : Background: Treacher Collins syndrome (TCS), the most common type of mandibulofacial dysostosis (MFD), is genetically homogeneous. Other types of MFD are less common and, of these, only the Bauru type of MFD has an autosomal dominant (AD) mode of inheritance established. Here we report clinical features of a kindred with a unique AD MFD with the exclusion of linkage to the TCS locus ( TCOF1 ) on chromosome 5q31-q32. Methods: Six affected family members underwent a complete medical genetics physical examination and two affected subjects had skeletal survey. All available medical records were reviewed. Linkage analysis using the markers spanning the TCOF1 locus was performed. One typically affected family member had a high resolution karyotype. Results: Affected subjects had significant craniofacial abnormalities without any significant acral changes and thus had a phenotype consistent with a MFD variant. Distinctive features included hypoplasia of the zygomatic complex, micrognathia with malocclusion, auricular abnormalities with conductive hearing loss, and ptosis. Significantly negative two point lod scores were obtained for markers spanning the TCOF1 locus, excluding the possibility that the disease in our kindred is allelic with TCS. High resolution karyotype was normal. Conclusions: We report a kindred with a novel type of MFD that is not linked to the TCOF1 locus and is also clinically distinct from other types of AD MFD. Identification of additional families will facilitate identification of the gene causing this type of AD MFD and further characterisation of the clinical phenotype.